Disruption of Darna pallivitta (Lepidoptera: Limacodidae) by Conventional and Mobile Pheromone Deployment. Issue 1 (13th June 2015) - Siderhurst, Matthew S.; Jang, Eric B.; Carvalho, Lori A. F. N.; Nagata, Janice T.; Derstine, Nathan T.
Abstract : Identification of the Darna pallivitta (Moore) pheromone component n-butyl ( E )-7, 9-decadienoate ( E 7, 9-10:COOn-Bu) has made it possible to investigate communication disruption to control this lepidopteran pest. Conventional communication disruption trials showed marked decreases in the mean number of male moths captured in E 7, 9-10:COOnBu-treated fields compared with control fields. For traps baited with E 7, 9-10:COOnBu, percent disruptions were 94.4% and 92.1% for septa (1 g pheromone/ha, 1-wk trial duration) and spirals (6 g pheromone/ha, 8-wk trial duration) respectively. For traps baited with virgin female moths, percent disruption was 73.3% using septa disruptors (1 g pheromone/ha, 1-wk trial duration). Mobile communication disruption using Bactrocera cucurbitae (Coquillett) as carriers for E 7, 9-10:COOn-Bu was evaluated in the following three areas: fly survivorship, attraction of male moths to treated flies, and moth disruption in a small-scale field trial. Topical application of E 7, 9-10:COOnBu showed no significant decrease in survivorship at 50 and 80 µg/fly. However, decreased survivorship was observed at 100 µg/fly and linear regression showed E 7, 9-10:COOnBu dose was significantly correlated with B. cucurbitae survivorship. Traps containing honey–pheromone-fed flies attracted and caught D. pallivitta over a 1-wk period, demonstrating the attractiveness of the carrier. Releasing E 7, 9-10:COOnBu-fed B. cucurbitae (∼2 g pheromone/ha, 1-wk trial duration) resulted in significantly reduced trap catches in treatment fields compared with control fields on the first 2 d of the field trial. Percent disruptions were 84.7% (day 1) and 56.0% (day 2). These results suggest that both conventional communication disruption and mobile communication disruption have potential to control D. pallivitta .